CHARACTERISTICS OF THE CONSTITUENT ELEMENTS OF A CRIMINAL OFFENCE – PERSECUTION - Kipāne, Aldona (Administrative and Criminal Justice, 2021)
From January 1, 2018, amendments to the Criminal Law, which provide criminal liability for the persecution of a person, came into force in Latvia. The constituent elements of persecution are defined as a specific form of violence.The aim of the paper is to describe the constituent elements of persecution based on the theory and practice of criminal law. During the study, the author provides a framework of the criminal law theory and outlines the elements of the persecution. The object of the study is the criminal relations, which arise from the persecution of another person. The subject of the study is the criminal legal framework to be followed for the determination of criminal liability. The following legal interpretation methods and approaches have been used in the study: grammatical, systematic, teleological, and historical, as well as analytical method for analysing doctrine and practice of criminal law. Doctrines of criminal law, national legislation, and the sources of legal literature relevant to the aim of the paper have been in the study, too.The analysis carried out leads to the conclusion that persecution covers a wide range of socio-psychological behaviour that manifests in the sacrifice’s victimization and specific harm caused to him/her. Persecution is an active illegal, threatening activity in the form of repeated or lasting tracking, surveillance of another person, expressing threats or unsolicited communication with such a person, if victim have had reasonable grounds to fear for their safety or the safety of their relatives